A Study of Extrusion Shear and Forced Convection Residence Time in The Spinning of Polysulfone Hollow Fiber Membranes for Gas Separation - Sharpe, I. D. (Elsevier, 1999)
Polysulfone hollow fiber membranes for gas separation were spun using a forced convection technique. Experiments were designed to decouple the effect of extrusion shear from forced convection residence time in the dry gap allowing both factors to be investigated. The main objective was to study the pure influence of shear and its capacity to increase membrane selectivity. The results suggested that extrusion shear influences phase inversion dynamics. Increasing shear decreased active layer thickness and increased pressure-normalized flux. This was discussed in terms of thermodynamic instability and polymer precipitation/coalescence speed. Increasing shear was found to increase selectivity to levels greater than the intrinsic value for the amorphous membrane polymer. This may be as a result of induced molecular orientation in the active layer. However, a critical shear rate existed beyond which selectivity deteriorated. This was attributed to the development of surface pores as the active layer thins. Membranes spun at intermediate forced convection residence times exhibited the highest selectivities. Skin formation must be complete, but excessive residence time allows deleterious non-solvent encroachment from the lumen. The results indicate that if enhanced selectivity and high flux are to be achieved, membranes should be spun at a high shear rate and an optimized residence time in order to minimize surface defects, increase the critical shear rate, decrease active layer thickness and heighten molecular orientation.